Answer: 6 I belive
Step-by-step explanation:
The answer would be A-72cm^2
Answer: 4
Step-by-step explanation:
so you basically make the + sign into a - sign as when there is a + and - sign next to each other it will always change into a - sign so once you do that it will look like this
11+(-7)
11-7
4
Answer:
<em>C) 7</em>
Step-by-step explanation:
<u>Quadratic equation</u>
The quadratic equation can be written in several ways, one of the most-used is
![ax^2+bx+c=0](https://tex.z-dn.net/?f=ax%5E2%2Bbx%2Bc%3D0)
To rewrite the equation in the form
![(x-p)^2=q](https://tex.z-dn.net/?f=%28x-p%29%5E2%3Dq)
we can complete squares and rearrange the terms as follows. The provided equation is
![x^2+18x+74=0](https://tex.z-dn.net/?f=x%5E2%2B18x%2B74%3D0)
The second term can be seen as
![2(x)(9)](https://tex.z-dn.net/?f=2%28x%29%289%29)
And the first two terms can be visualized as the square of a binomial
![x^2+2(x)(9)+81-81+74=0](https://tex.z-dn.net/?f=x%5E2%2B2%28x%29%289%29%2B81-81%2B74%3D0)
We have added and subtracted 81 to complete the square and not modify the equation. The new form of the equation is
![(x+9)^2-7=0](https://tex.z-dn.net/?f=%28x%2B9%29%5E2-7%3D0)
Rearranging
![(x+9)^2=7](https://tex.z-dn.net/?f=%28x%2B9%29%5E2%3D7)
Comparing with the general form written above, we find that
![\boxed{q=7}](https://tex.z-dn.net/?f=%5Cboxed%7Bq%3D7%7D)